Barriers to the effective adoption of learning management systems in higher education: A case study in South Africa - Masibigiri, Percy; Dandadzi, Alex; Seeletse, Solly (Edelweiss Applied Science and Technology, 2026)
This study investigates the barriers to effective Learning Management System (LMS) adoption in South African higher education institutions, focusing on connectivity, digital content quality, and technical support challenges. A mixed-methods approach was employed, combining a systematic literature review (SLR) of articles published between 2015 and 2025 with a quantitative survey. A questionnaire was distributed to students enrolled in a distance learning module, yielding 337 responses from 455 students (74% response rate). The SLR revealed that poor internet infrastructure, high data costs, inadequate digital content localization, and insufficient technical support significantly impede LMS adoption. The quantitative survey confirmed these findings: 51% of respondents reported connectivity problems, 42.7% experienced content-related issues, and 46.3% encountered support challenges. These barriers disproportionately affect rural and peri-urban students, reinforcing the digital divide. Infrastructural inequalities, content development gaps, and weak institutional support structures limit effective LMS integration in South African universities. The study recommends addressing infrastructural disparities, enhancing localized digital content development, strengthening institutional support systems, and implementing government policies to standardize LMS adoption, particularly for resource-constrained rural institutions.